PERKEMBANGAN BENTUK KERAJINAN CUKLI DI LINGKUNGAN RUNGKANG JANGKUK DESA SAYANG-SAYANG KOTA MATARAM - Pyo Apriliana Munawarah (Gelar : Jurnal Seni Budaya, 2014)
The article is the research result about the form of cukli craft in Rungkang Jangkuk, village of Sayang-Sayang, Cakranegara, Mataram City, Nusa Tenggara Barat. The research problems include the existence orthe appearance as well as the development of form in cukli wood craft. A term of cukli means a process ofholing or picking a bit of the wood surface to insert the seashells that is formed in accordance to theornament style wanted. The research uses qualitative method. Interactive analysis is used for data stabilizationand exploration then compared with the related data in accordance to the research aim. Interpretation analysisrefers to the development of the form of cukli craft especially in Rungkang Jangkuk area. The creatingprocess is precisely influenced by internal and external factors. The form of cukli craft has many benefits aswell as function values that meet the buyers’ taste. The product of cukli can be categorized as a craft thathas aesthetic values which uses technique of cukil in the making process. Cukli craft becomes moreinteresting for the actors and lovers of the classical ethnic model that it gets to be an image of Lombokculture and it becomes more developing in its form as well as ornament. The existence of all products of cukliin Lombok that is still developing until now is a process of creativity that has a wonderful attractiveness forthe domestic as well as foreign country tourists who come to LombokKeywords: development, creativity, form, ornament, cukli craft